'It's a hard conversation to have'. Healthcare professionals' views concerning advance care discussions with young people affected by life-limiting neuromuscular diseases: an interview study. Issue 1 (19th June 2017) - Hiscock, Andy; Barclay, Stephen
Abstract : Objective: Life-limiting neuromuscular disease, such as some of the muscular dystrophies, are often diagnosed in early childhood: when death comes, commonly in the second or third decade of life, patients rarely have advance care plans in place or documented end-of-life care preferences. There is very limited literature concerning the discussions about end-of-life plans healthcare professionals have with young people affected by life-limiting neuromuscular diseases. The aim of this study was to investigate the views and experiences of healthcare professionals concerning having discussions about advance care plans and end-of-life care with teenagers and young adult patients affected by life-limiting neuromuscular diseases. Methods: Semistructured interviews with a maximum variety sample of nine professionals involved in the care of young people with life-limiting neuromuscular diseases in one region of the UK. Results: While recognising the inevitable progression of the conditions, there was no consensus among interviewees concerning best approaches to discuss end-of-life care plans. Several environmental and personal barriers were identified that lead to avoidance of the emotionally challenging and difficult conversations. Conclusions: Community-based professionals with well-established relationships with patients and families may be best placed to take the lead and coordinate discussions, but individual case-by-case preferences need to be carefully considered.